Straits settlements Blue Book miscellanea (imports/exports) 1889-1890 vol.28-29 (Great Britain : Public Record Office, 1971)
Mengandungi' Blue Book for the Year 1890';'Return of imports and exports for the year 1890';'Statement of the value of imports into and exports from the three settlements during the year 1890'';''Recapitulatory and comparative statement of the value of imports into and exports from the colony of Straits Settlements during the year 1890'';''Report on Straits Settlements Blue Book for the year 1890''.